Committee on board: Does it matter? A study of Indonesian Sharia-listed firms - Fauzi, Fitriya; Basyith, A.; Foo, D. (Cogent OA, 2017)
© 2017 The Author(s). The committee on board includes audit committee and nomination committee that currently has been questioned as to whether the firm value is also affected by the committees’ performance that has been the subject of attention. Apparently, this study is the first to attempt providing an evidence of committees’ role on to the extent of its contribution to firm value in the context of Indonesian Sharia-listed firms as the establishment of Islamic-compliance firms is currently experiencing an upward trend in many countries. Hence it is enticing to examine the impact of committee on board as part of corporate governance mechanisms on firm value in the Indonesian Sharia-listed firms. Using an Indonesian Sharia-listed firms which counts for 30 firms in the quarterly period of 2009 to 2015, this study employs a 720 balanced panel, using Generalized Least Square. The results reveal that the audit committee and the nomination committee have a significant impact on firm value (Tobin’s Q). The non-significant result for ROA suggesting that the mixed measured of book and market is viewed more reliable for investors as it indicates the overall performance measure. Meanwhile the result of the number of audit committee meeting yielded no significant impact on firm value; this may be due to no restrictions on the number of positions of audit committee serves in firms, therefore, the auditor may be manifold in some companies which can be overlapping. Further, the number of audit committee only meets the regulations and yet the transparency is still far beyond.